Histopathological Alterations in the Gills of Freshwater Fish, Puntius ticto on Exposure to Distillery Effluent - T.S. Pathan2* and Y.K. Khillare3, P.B. Thete1, Kshma Khobragade1 (Journal of Experimental Sciences, 2010)
Fresh water fish Puntius ticto exposed to lethal concentrations (25% and 22% for 24h and 96h of LC50) of distillery effluent, showed pronounced histopathological alterations in the gills, such as cloudy swelling in chloride and pillar cells. Fusion of secondary lamellae and blood hemorrhages at some places were also observed in 24h exposure. Fusion and cytoplasmic degenerations were also observed in secondary gill lamellae along with cell necrosis. Hypertrophy of epithelial cells with pyknotic nuclei have been noticed in pillar cells on 96h exposure.